Liposomal Delivery of MIW815 (ADU-S100) for Potentiated STING Activation - Nan Ji; Minjia Wang; Chalet Tan (MDPI AG, 2023)
Stimulator of interferon genes (STING) agonists can improve the anticancer efficacy of immune checkpoint blockade by amplifying tumor immunogenicity. However, the clinical translation of cyclic dinucleotides (CDNs) as STING agonists is hindered by their poor drug-like properties. In this study, we investigated the design criteria for DOTAP/cholesterol liposomes for the systemic delivery of ADU-S100 and delineated the impact of key formulation factors on the loading efficiency, serum stability, and STING agonistic activity of ADU-S100. Our findings demonstrate that the cationic liposomal formulation of ADU-S100 can be optimized to greatly potentiate STING activation in antigen-presenting cells.